Implementing a digital health pathway for pediatric tracheostomy: a qualitative descriptive study of barriers, facilitators, and implementation strategies informed by the CFIR–ERIC Matching Tool - Daniel Ofosu; Nadia Qureshi; Sela Scott; Joanna Czupryn; Gabrielle Zimmermann; Karen Kam; Michael van Manen; Maria Castro-Codesal (BMC Health Services Research, 2026)
Abstract Background Children requiring tracheostomy often have chronic, complex medical conditions that require coordinated, multidisciplinary care across hospital and home settings. DECIDE-T (Digital hEalth pathway for ChIldren with meDical complExity requiring Tracheostomy) is a multicenter digital innovation designed to standardize pediatric tracheostomy care in Alberta, Canada. This pre-implementation study aimed to identify the perceived determinants of implementing the DECIDE-T care pathway and to develop theory-informed, context-appropriate implementation strategies. Methods We conducted a qualitative descriptive study involving healthcare providers from two pediatric tertiary care centers and their affiliated outpatient clinics and homecare programs. Participants completed an open-ended survey, and some also participated in follow-up semi-structured interviews. Qualitative data were analyzed using deductive content analysis guided by the Consolidated Framework for Implementation Research (CFIR). Identified barriers were matched to implementation strategies using the CFIR–Expert Recommendations for Implementing Change (ERIC) Matching Tool, and the strategies were operationalized via the reporting recommendations of Proctor et al. Results Healthcare providers identified a supportive organizational culture, engagement of intervention deliverers, and the need for standardized care as key facilitators of DECIDE-T implementation. Major barriers included limited accessible evidence, communication and resource challenges, and variability in staff knowledge, self-efficacy, and role clarity. Mapping these barriers to the CFIR–ERIC Matching Tool generated implementation strategies emphasizing education, organizational support, and engagement of implementation partners through local champions and opinion leaders. Conclusions Successful implementation of the DECIDE-T care pathway requires strategies that address technical, individual, organizational, and system-level determinants. The theory-informed, context-tailored approach used in this study may inform implementation planning for other digital care pathways for children with medical complexity across diverse care settings.